2016
DOI: 10.1002/bies.201600101
|View full text |Cite
|
Sign up to set email alerts
|

A Pseudomonas aeruginosa‐secreted protease modulates host intrinsic immune responses, but how?

Abstract: Recently, we found that the Pseudomonas aeruginosa type II secreted protease IV functions as a unique Arabidopsis innate immunity elicitor. The protease IV-activated pathway involves G protein signaling and raises the question of how protease elicitation leads to the activation of G protein-mediated signaling, because plants do not appear to have metazoan-like G protein-coupled receptors. Importantly, our data suggest that Arabidopsis has evolved a mechanism to detect the proteolytic activity of a pathogen-enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 118 publications
(158 reference statements)
0
6
0
Order By: Relevance
“…Similarly nano-vaccine developed using outer membrane protein (OmpW) of Aeromonas hydrophila showed a dose dependent Immunity in Rohu sh(Labeo rohita) [41]. Recent research enlightened Pseudomonas aeruginosa as immune elicitor by secreting type II protease IV functions in Arabidopsis [42]. Protease IV activates pathway involving G protein signaling in immune function.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly nano-vaccine developed using outer membrane protein (OmpW) of Aeromonas hydrophila showed a dose dependent Immunity in Rohu sh(Labeo rohita) [41]. Recent research enlightened Pseudomonas aeruginosa as immune elicitor by secreting type II protease IV functions in Arabidopsis [42]. Protease IV activates pathway involving G protein signaling in immune function.…”
Section: Discussionmentioning
confidence: 99%
“…DAMPs are danger signals originated from the host because of deleterious activities of microbial hydrolytic enzymes (Gust et al , 2017). As bacterial proteases PrpL, secreted by Pseudomonas aeruginosa , and ArgC, by Xanthomonas campestris , can activate an immune response in Arabidopsis that includes induction of an oxidative burst (Cheng et al , 2015), it appears that plants have evolved a mechanism to detect the proteolytic activity of pathogen-encoded proteases (Cheng et al , 2015; Cheng, 2016). Although it remains to be determined how the protease triggers the activation of the immune pathway (Cheng, 2016), it has been suggested that pathogen-secreted proteases could release host polypeptides that function as DAMPs and are subsequently recognized by immune receptors (Cheng et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains to be determined how the protease triggers the activation of the immune pathway (Cheng, 2016), it has been suggested that pathogen-secreted proteases could release host polypeptides that function as DAMPs and are subsequently recognized by immune receptors (Cheng et al , 2015). This mechanism, or a similar one (Cheng, 2016), appears to occur in red rice seeds too. As P. aeruginosa is an opportunistic bacterial pathogen and X. campestris is a true pathogen, whereas S. griseus is non-pathogenic, the mechanism to detect the proteolytic activity of damaging microbial proteases might be a rather generic one.…”
Section: Discussionmentioning
confidence: 99%
“…Protease IV is significantly associated with corneal virulence of P. aeruginosa ( Bradshaw et al., 2018 ). Not only can protease IV interfere with host immunity by degrading various biologically important molecules, such as complement components, immunoglobulins, and surfactant proteins, but also damage host tissues and enhance bacterial infection through degradation of fibrinogen, lactoferrin, transferrin, and elastin ( Engel et al (1998) ; Malloy et al., 2005 ; Cheng, 2016 ; O'Callaghan et al., 2019 ). Since protease IV is a serine protease, known serine protease inhibitors that block its enzymatic activity may be developed into therapeutics to prevent tissue damage caused by P. aeruginosa infection.…”
Section: The Virulence Factors Of P Aeruginosamentioning
confidence: 99%